Factors Affecting the Local Governments Financial Performance - Oktaviani, Regita; Wijaya, Satria Yudhia; ., ermawati (Journal of Economics and Behavioral Studies, 2020)
This study aims to test and prove the relationship of local government financial performance with fiscal balance transfer, local own-source revenue, local government size, and capital expenditure. The study uses samples from District/City Local Governments in Sulawesi Island for the years 2016-2018. The samples were collected using the census sampling method, for a total of 243 samples in District/City Local Governments in Sulawesi Island. In this analysis, the hypothesis testing is performed using SPSS by the multiple linear regression method. The result of this study shows that fiscal balance transfer has a negative impact on the local government financial performance, local own-source revenue has an impact towards the local government financial performance, local government size does not have an effect towards the local government financial performance, and capital expenditure has an effect towards the local government financial performance. This study is expected to contribute to local governments by providing recommendations to improve the local government financial performance.